Cyberbullying: teen bullying through Facebook social network - Astrid Carolina Gómez Almanza; Diana Castillejo; Germán Vargas (Corporación Universitaria Minuto de Dios, 2013)
The aim of this paper was to describe how well a group of sixth-grade youth belonging to Leon de Greiff district school district from the city of Bogotá, DC, were suffering in their school life due to the inappropriate use of Facebook. The research was a qualitative one with case study design and a sample of 16 female students between 11 and 13 years old. In the data collection, interviews, field diaries / logs, participant observation and recording technology systems were used. To triangulate the information, the IT program ATLAS, where categorised according to context, cyber bullying, information, intimidation, Facebook and subject analysis were used. A process of coding, categorization and conceptual level was performed. The results showed that 16 students used Facebook with intimidating for direct, indirect or social / relational bullying manner.